Comparison of TDMA (GSM) and W- CDMA (3G) Systems Based on their Modulation Techniques - Olusanya Olamide O.; Ogunseye Abiodun A (Current Approaches in Engineering Research and Technology Vol. 4, 2024)
In recent years, cellular communication has experienced exponential growth, and the growth continues unabated worldwide, with cell phone users numbering billions. Mobile network communication system offers users seamless communication and this has caused wireless communication to increasingly become the preferred method of carrying multimedia traffic or messages such as voice, video, images, and data files. Time division multiple access (TDMA) is the multiple access scheme used in global systems for mobile communication (GSM), while third-generation (3G) system uses wideband-code division multiple access (W-CDMA). The former is designed mainly for voice and a little of data. Due to the increase in the number of phone users and the services enjoyed by the users, there is a higher demand for non-voice services, mobile extensions to fixed-line services and richer mobile content. This has caused the network operators to develop 3G systems with the goal of providing a network infrastructure that can support a much broader range of services than existing systems in which its penetration level has reached market saturation. This paper presents a comparison of the two wireless systems' performance based on their modulation techniques. Simulation of their modulation techniques using MATLAB was carried out. From the constellation obtained, the two systems were analyzed and the analysis shows that W-CDMA (that is, 3G) provides a network infrastructure that can support a much broader range of services than existing systems (GSM) because the main forces behind the development of the 3G have been driven by the second-generation systems’ low-performance data services, incompatible service in different parts of the world, and lack of capacity. Moreover, 3G systems also have higher security compared to GSM systems because all signals are separated from each other by means of special code since they all use the same frequency channel at the same time.